Bipolar Choquet integral of fuzzy events - Abbas, Jabbar (2014 IEEE Symposium on Computational Intelligence in Multi-Criteria Decision-Making (MCDM), 2014)
The aim of this paper is to propose the concept of bi-capacities and its integrals of fuzzy events. First, we introduce a approach for studying bi-capacities of fuzzy events. Then, we propose a model of bipolar Choquet integral with respect to bi-capacities of fuzzy events, and we give some basic properties of this model.